Sensing inhomogeneous mechanical properties of human corneal Descemet's membrane with AFM nano-indentation. (October 2017) - Di Mundo, Rosa; Recchia, Giuseppina; Parekh, Mohit; Ruzza, Alessandro; Ferrari, Stefano; Carbone, Giuseppe
Abstract: The paper describes a highly space-resolved characterization of the surface mechanical properties of the posterior human corneal layer (Descemet's membrane). This has been accomplished with Atomic Force Microscopy (AFM) nano-indentation by using a probe with a sharp tip geometry. Results indicate that the contact with this biological tissue in liquid occurs with no (or very low) adhesion. More importantly, under the same operating conditions, a broad distribution of penetration depth can be measured on different x-y positions of the tissue surface, indicating a high inhomogeneity of surface stiffness, not yet clearly reported in the literature. An important contribution to such inhomogeneity should be ascribed to the discontinuous nature of the collagen/proteoglycans fibers matrix tissue, as can be imaged by AFM when the tissue is semi-dry. Using classical contact mechanics calculations adapted to the specific geometry of the tetrahedral tip it has been found that the elastic modulus E of the material in the very proximity of the surface ranges from 0.23 to 2.6 kPa.